Pattern of Suicidal Deaths in Females- A Cross Sectional Study in the Age Group of 12-24 Years - Kandagatla Krishnamurthy; S.M. Krishna Sagar; Abhijith Subedhar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Suicide is the fourth leading cause of death among young males and the third for young females, globally. Suicide affecting the youth is a big loss to the community. Hence, the aim of this study is to identify pattern of suicidal deaths in females belonging to 12-24 years age group.Methods: A cross sectional study was conducted in the Department of Forensic Medicine, Gandhi Medical College, Secunderabad, which included all the deaths that occurred due to suicide in females aged 12-24 years from January 2017 to November 2018. Results: Most victims belonged to the age group of 19-24 years (49%) and were from rural area (60%). Majority attempted suicide during day time (72%) and inside their own homes (89%). In 91% of the cases, there was no history of previous attempt and in 92%, no suicide note was found. 55% of deaths occurred on the spot. Most common method of suicide was hanging (53%).Conclusion: Suicide is a growing public health concern amongst the young. Peer support groups for adolescents and young adults, who have exhibited suicidal behaviours, must be established to help prevent repeated attempts.